Kombinasi Algoritma Sequential Searching dan Bubble Sort Pada Manajemen Laboratorium - Arifin, Nur; Fauziah, F; Nurhayati, N (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
The facilities in the laboratory can make students especially feel comfortable because of several supports such as internet availability, better computer specifications, servers with large capacities as data storage media and rooms that support students' conditions in doing their assignments. During the pandemic, the laboratory cannot be used optimally because learning is done online. So that an online application for borrowing a laboratory is needed to maximize the function of the laboratory. In this study, a laboratory loan website application was designed by combining sequential search and bubble sort algorithms on the search engine menu so as to facilitate and speed up the process of searching for laboratory types. The test was carried out simultaneously from 700 test data and resulted in a time of 3 milliseconds for the sequential search algorithm, and 0.036 milliseconds for the bubble sort algorithm. While the results of the testing time with the combination of the two algorithms obtained are 4 milliseconds